Design de moda e tecnologia têxtil: projetos ergonômicos de Nanni Strada e Issey Miyake - FERREIRA, Veridianna Cristina Teodoro (2016)
The present paper focuses on the contribution to fashion design, through the use of existing technologies in the tissues, which associated with an appropriate modeling, whose objective is in the attribution of comfort to the user, respect for the health of his body and its skin freedom of movement. The work, especially, intend to present a way to respect for the different existing body forms, without the body having to change its forms to suit a garment. The propose is reach this through the use of technological fabrics. The work propose a dialogue between textile technology and ergonomic, mainly related to anthropometric measures, to develop a dress that respects the architecture of the user's body. This study analyzed how ergonomics defends the user's pleasure in using the product and what characteristics should be contained in a garment, in order to the user perceives the space occupied by the clothing. To support this discussion and these forms of designing a garment, the works "Torchon" and "Pli Plá" by Nanni Strada (2008) and "Pleats Please" by Issey Miyake (2012) were presented, because both fashion designers start from these concerns with the individual, in developing their dress designs. In addition, is correct to say that their works fit the premises of a universal ergonomic design, whose purpose is precisely to tailor clothing to different bodies, heights and body shapes. In this sense, this work aims to discuss the existing technologies in the textile market, whose purpose is to favor clothing in contact with the body, respecting their forms, mobility, health, comfort and tactile perception of clothing to the body. It also discusses proposals that deal with dressing whose concern is the suitability of clothing in different body shapes, whose solution tool is the technological innovations in the textile field.